2019
DOI: 10.1038/s41418-019-0381-y
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA PVT1 regulates nasopharyngeal carcinoma cell proliferation via activating the KAT2A acetyltransferase and stabilizing HIF-1α

Abstract: Long noncoding RNAs (lncRNAs) play important roles in regulating the development and progression of many cancers. However, the clinical significance of specific lncRNAs in the context of nasopharyngeal carcinoma (NPC) and the molecular mechanisms by which they regulate this form of cancer remain largely unclear. In this study we found that the lncRNA PVT1 was upregulated in NPC, and that in patients this upregulation was associated with reduced survival. RNA sequencing revealed that PVT1 was responsible for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
134
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 42 publications
4
134
0
Order By: Relevance
“…Some lncRNAs have gradually become important regulators in the development of hypoxic tumors [ 147 ]. In nasopharyngeal carcinoma cells (NPC), both lncRNA PVT1 and lncRNA DANCR can interact with HIF-1α to influence NPC progression [ 148 , 149 ]. Plasmacytoma variant translocation 1 (PVT1) is the first lncRNA gene discovered in Burkitt’s lymphoma, and its lncRNA that has been reported to play a role in promoting tumor progression [ 147 ].…”
Section: Epigenetic Regulation Of Hifs Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some lncRNAs have gradually become important regulators in the development of hypoxic tumors [ 147 ]. In nasopharyngeal carcinoma cells (NPC), both lncRNA PVT1 and lncRNA DANCR can interact with HIF-1α to influence NPC progression [ 148 , 149 ]. Plasmacytoma variant translocation 1 (PVT1) is the first lncRNA gene discovered in Burkitt’s lymphoma, and its lncRNA that has been reported to play a role in promoting tumor progression [ 147 ].…”
Section: Epigenetic Regulation Of Hifs Activitymentioning
confidence: 99%
“…Plasmacytoma variant translocation 1 (PVT1) is the first lncRNA gene discovered in Burkitt’s lymphoma, and its lncRNA that has been reported to play a role in promoting tumor progression [ 147 ]. PVT1 activates the acetyltransferase KAT2A, and then recruits TIF1β to promote the transcription of NF90 [ 148 ]. This improves the stability of HIF-1α protein and mRNA, and promotes further hypoxia-induced malignant phenotype of NPC [ 148 ].…”
Section: Epigenetic Regulation Of Hifs Activitymentioning
confidence: 99%
“…In recent years, CRC with increasing morbidity and mortality rate has become one of the most common malignant tumors 30 . It has been reported that several lncRNAs are aberrantly expressed in CRC and regarded as vital components of cancer risk 31,32 . For instance, Zhang et al 33 identified the downregulation of lncRNA CPS1‐IT1 in CRC cells, and CPS1‐IT1 overexpression suppresses metastasis through inactivating HIF‐1α in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative radiotherapy is one of the main modalities of GBM treatment, but it often fails to achieve the expected results mainly due to tumor radioresistance. Increasing studies showed that lncRNAs have been found to modulate radiosensitivity by regulating various mechanisms [27].Wang et al reported that lncRNA PVT1 served an oncogenic role and played an important role in radiosensitivity in malignant nasopharyngeal carcinoma via activating the KAT2A acetyltransferase and stabilizing HIF-1α [28]. Another study suggested that lncRNA TP73-AS1 was highly expressed in hepatocellular carcinoma and participated in radioresistance via PTEN/AKT signaling pathway [29].…”
Section: Discussionmentioning
confidence: 99%